胶束毛细管电泳法检测IL-12的含量 (Nan Fang Yi Ke Da Xue Xue Bao, 2020)
OBJECTIVE: To establish a micellar electrokinetic capillary chromatography-based method for identification and quantitative detection of interleukin-12 (IL-12) and analysis of its unfolding process. METHODS: An uncoated fused-silica capillary (inner diameter 50 μm) with a total length of 48.5 cm (40 cm to the detector) was used for the experiment. The factors influencing the separation efficiency of IL-12 were analyzed, and a standard curve of IL-12 concentration was established. The mixture of IL-12 and anti-IL-12 antibody was incubated in a water bath at 38 ℃ for 40 min, and capillary electrophoresis was then performed under the same conditions. The results were compared with those of IL-12 and anti-IL-12 antibody to identify IL-12. IL-12 and dithiothreitol (DTT) were incubated at 60 ℃ in water bath for different lengths of times, and the unfolding process of IL-12 was analyzed based on electrophoresis results of IL-12 in different states. RESULTS: A micellar capillary electrophoresis on-line sweep method was established with 80 mmol/L borate (pH=9.3) containing 30 mmol/L sodium dodecyl sulfate (SDS) as the buffer solution. This system showed a good linear relationship between the peak area and the mass concentration of IL-12 with a linear correlation coefficient of 0.9991 within the linear range of 2 to 120 ng/L. As the incubation time of IL-12 and DTT prolonged, the disulfide bond of IL-12 gradually opened and resulted in distinct changes in the protein peak. CONCLUSION: This capillary electrophoresis-based method is simple and sensitive for IL-2 analysis and allows rapid detection of changes in IL-12 content in the setting of tumors and analysis of the possible causes.